2021
DOI: 10.1038/s41598-021-89564-y
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal forecasts offer economic benefit for hydrological decision making in semi-arid regions

Abstract: Increasing frequencies of droughts require proactive preparedness, particularly in semi-arid regions. As forecasting of such hydrometeorological extremes several months ahead allows for necessary climate proofing, we assess the potential economic value of the seasonal forecasting system SEAS5 for decision making in water management. For seven drought-prone regions analyzed in America, Africa, and Asia, the relative frequency of drought months significantly increased from 10 to 30% between 1981 and 2018. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…While meteorological to hydrological drought is forecasted at a monthly to the seasonal time scale in practice 91 , timely issuance of targeted drought early warning systems (DEWS) 92 and a dynamical low flow forecast at a higher temporal resolution involving primary drought attributes, such as growth, persistence and recovery pattern, could be effective in mitigating impacts. Further, for climatologically heterogeneous regions of India, developing an improved probabilistic S2S low flow forecast, integrating the static and dynamic controls could be of great interest in aiding economic resilience to droughts 93 .…”
Section: Discussionmentioning
confidence: 99%
“…While meteorological to hydrological drought is forecasted at a monthly to the seasonal time scale in practice 91 , timely issuance of targeted drought early warning systems (DEWS) 92 and a dynamical low flow forecast at a higher temporal resolution involving primary drought attributes, such as growth, persistence and recovery pattern, could be effective in mitigating impacts. Further, for climatologically heterogeneous regions of India, developing an improved probabilistic S2S low flow forecast, integrating the static and dynamic controls could be of great interest in aiding economic resilience to droughts 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed this issue, showing that better skill does not always result in positive value (Boucher et al, 2012;Chiew et al, 2003). Although, in terms of 'skill', earlier findings argue that SFFs are generally less skilful than ESP (e.g., Lucatero et al, 2018;Yossef et al, 2013), in terms of 'value', a recent study has demonstrated that the use of seasonal forecasts in semi-arid regions offers significant economic benefits by mitigating hydro-energy losses in a dry year (Portele et al, 2021). Therefore, our future research efforts should concentrate on a quantitative evaluation of the value of SFFs for reservoir operations to informing decision-making in water resources management.…”
Section: The Skill Of Seasonal Flow Forecastsmentioning
confidence: 97%
“…In the agricultural sector, for example, a recent study shows that flowering time can be reliably predicted from seasonal meteorological forecasts in central and eastern Europe, enabling early variety selection and planning of farm management (Ceglar and Toreti, 2021). Seasonal meteorological forecasts were also shown to provide useful information for the wind energy sector (Lledó et al, 2019) and to avoid significant economic losses from hydropower generation during droughts (Portele et al, 2021). Nevertheless, the use of seasonal meteorological forecasts for water temperature in lakes and reservoirs has been limited so far, where the focus has been on water quantity (Arnal et al, 2018;Giuliani et al, 2020;Greuell et al, 2019;Pechlivanidis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%